EVALUATION OF THE TOXICITY AND REVERSIBILITY PROFILE OF THE AQUEOUS SEED EXTRACT OF HUNTERIA UMBELLATA (K. SCHUM.) HALLIER F. IN RODENTS - Adeneye, A. A.; Adeyemi, O. O.; Agbaje, E. O.; Banjo, A. A. F. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Hunteria umbellata (K. Schum.) Hallier f. (family: Apocynaceae) is reputed for the folkloric management of labour, pain and swellings, stomach ulcers, diabetes, obesity, and anaemia, with no scientific report of its toxicity and reversibility profile. The present study was, therefore, aimed at investigating the in vivo toxicity and reversibility profile of the aqueous seed extract of Hunteria umbellata (HU). The acute oral and intraperitoneal toxicity studies of HU were determined in Swiss albino mice while its 90-day oral toxicity and toxicity reversibility profile on anthropometric, biochemical, haematological and histopathological parameters were also assessed using standard procedures. Results showed that the LD 50 values for the acute oral and intraperitoneal toxicity studies for HU were estimated to be 1000 mg/kg and 459.3 mg/kg, respectively. Visible signs of immediate and delayed toxicities including starry hair coat, respiratory distress, and dyskinesia were observed. For the chronic oral toxicity study, HU administered for 90 days produced significant (p<0.001) reductions in the weight gain pattern and significant (p<0.001) and dose related increases in the relative weights of liver, stomach, spleen, testis, lungs and heart, at the 100 and 500 mg/kg of HU. Chronic HU treatment also produced significant (p<0.05, p<0.001) dose related reductions in the serum levels of fasting blood glucose, bicarbonate, urea and creatinine while causing non-significant (p>0.05) alterations in the serum levels of sodium, potassium, alaninine transaminase, aspartate transaminase, alkaline phosphatase, total and conjugated bilirubin, total protein and albumin. Also, chronic oral treatment with HU produced significant (p<0.05, p<0.01, p<0.001) and dose-related increases in the red cell count, packed cell volume, haemoglobin concentration, platelet count, total leucocyte count and lymphocyte differential while producing significant (p<0.05) reductions in neutrophil and granulocyte differentials. HU also produced histological features of proliferations of the stomach epithelia, lung tissues, splenic white and red pulps, and testicular spermatogenic series. Following 14 days of oral toxicity reversibility test, there was no significant (p>0.05) reversal in the serum levels of the biochemical and haematological parameters investigated, including the HU-induced histological lesions. Overall, results of this study showed that HU has a relatively low oral toxicity profile but its prolonged use, particularly, at high doses should be with great caution.